The Importance of Integrating Education for Sustainable Development in Alternative Energy Assessment to Develop Students Critical Thinking Skills - Fadila, Ananta (Universitas Negeri Padang, 2025)
This study aims to analyze the need for developing electronic assessments of critical thinking skills integrated with Education for Sustainable Development (ESD) on alternative energy material for phase E students. The research used a quantitative descriptive approach with the 4D model. The research population was 78 students of class X phase E in the 2024/2025 school year at SMAN 10 Padang, with a sample of 39 students selected by random sampling. Data collection techniques used questionnaires, critical thinking skills tests based on Ennis' five indicators, and interviews with physics teachers. The results showed that students' critical thinking skills were still relatively low, especially in the basic support indicator (building basic skills) with a percentage of only 1.28%. Learners have difficulty in considering the credibility of sources, observing results, and making appropriate decisions. Meanwhile, learners' sustainability awareness is classified as very high (80-89%), but it is still partial because it only focuses on environmental aspects, not including economic, social and cultural dimensions as demanded by ESD. The interview results show that teachers have implemented critical thinking assessments and technology in learning, but have not optimally integrated ESD and did not include appropriate scoring rubrics. This research identified an urgent need to develop an electronic assessment of ESD-integrated critical thinking skills by utilizing digital platforms such as wizer.me. This assessment is expected to provide a relevant and meaningful context for learners in developing critical thinking skills through sustainability issues, while equipping them with a comprehensive understanding of sustainable development that covers all its dimensions.